Vertically aligned cupric oxide nanorods for nitrogen monoxide gas detection - Jong-Hyun Park; Hyojin Kim (Biuletyn Uniejowski, 2023)
Utilizing low-dimensional structures of oxide semiconductors is a promising approach to fabricate relevant gas sensors by means of potential enhancement in surface-to-volume ratios of their sensing materials. In this work, vertically aligned cupric oxide (CuO) nanorods are successfully synthesized on a transparent glass substrate via seed-mediated hydrothermal synthesis method with the use of a CuO nanoparticle seed layer, which is formed by thermally oxidizing a sputtered Cu metal film. Structural and optical characterization by x-ray diffraction (XRD), scanning electron microscopy (SEM), and Raman spectroscopy reveals the successful preparation of the CuO nanorods array of the single monoclinic tenorite crystalline phase. From gas sensing measurements for the nitrogen monoxide (NO) gas, the vertically aligned CuO nanorod array is observed to have a highly responsive sensitivity to NO gas at relatively low concentrations and operating temperatures, especially showing a high maximum sensitivity to NO at 200 ℃ and a low NO detection limit of 2 ppm in dry air. These results along with a facile fabrication process demonstrate that the CuO nanorods synthesized on a transparent glass substrate are very promising for low-cost and high-performance NO gas sensors. KCI Citation Count: 0